Glucose Tolerance and Insulin Action in Monosodium Glutamate (MSG) Obese Exercise-trained Rats - De Mello, Maria Alice Rostom [UNESP]; De Souza, Claudio Teodoro [UNESP]; Braga, Larissa Ribeiro [UNESP]; Dos Santos, Júlio Wilson [UNESP]; Ribeiro, Inand'Andrea [UNESP]; Gobatto, Claudio Alexandre [UNESP] (My University, 2001)
The present study was designed to evaluate the effects of chronic aerobic exercise (swimming, 1h/day, 5 days/week, with an overload of 5% body weight) on glucose metabolism in obese male Wistar rats. Hypothalamic obesity was induced through administration of monosodium glutamate (MSG) at 4 mg/g of body weight every other day from birth to 14 days old. Fourteen weeks after drug administration, the rats were separated into two groups: MSG-S (sedentary) and MSG-T (swimming for 10 weeks). Rats of the same age and strain, receiving saline in place of MSG, were used as control (C), and subdivided into two groups: C-S and C-T. At the end of the experimental period, an oral glucose tolerance test was performed and serum glucose (AG) and insulin (AI) were evaluated. A constant for serum glucose decrease (Kitt) in response to exogenous insulin was calculated. Soleus muscle strips and adipose tissue samples were incubated and insulin stimulated glucose uptake determined. No differences were observed in AG among the 4 groups. MSG-S rats showed higher AI (418%) and lower Kitt (92.3%) than C-S rats. T-rats showed higher glucose uptake by muscle (224.0%) and adipose tissues (94.1%) than S-rats. Among trained rats, glucose uptake by muscle was higher in MSG-T (5.4%) than in C-T. while the opposite was observed in adipose tissue (39% higher in C-T). Chronic aerobic exercise was able to improve glucose tolerance and reduce insulin resistance in MSG-obese rats. These effects were associated to an increase in glucose uptake by muscle and adipose tissue in response to insulin.
Keywords: food additive; glucose; glutamate sodium; insulin; lactic acid; adipose tissue; animal; animal experiment; blood; body composition; female; glucose blood level; glucose tolerance test; iatrogenic disease; male; metabolism; obesity; physiology; rat; rat strain; skeletal muscle; weight gain; Adipose Tissue; Animal; Blood Glucose; Body Composition; Female; Food Additives; Glucose; Glucose Tolerance Test; Insulin; Lactic Acid; Male; Muscle, Skeletal; Obesity; Physical Conditioning, Animal; Rats; Rats, Wistar; Sodium Glutamate; Support, Non-U.S. Gov't; Weight Gain